2019
DOI: 10.1038/s41467-019-12648-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic control of −1 programmed ribosomal frameshifting

Abstract: mRNA contexts containing a ‘slippery’ sequence and a downstream secondary structure element stall the progression of the ribosome along the mRNA and induce its movement into the −1 reading frame. In this study we build a thermodynamic model based on Bayesian statistics to explain how −1 programmed ribosome frameshifting can work. As training sets for the model, we measured frameshifting efficiencies on 64 dnaX mRNA sequence variants in vitro and also used 21 published in vivo efficiencies. With the obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…1). Mutations in the slippery sequence of dnaX were shown to decrease frameshifting efficiency to low ( 5%) or undetectable levels (Bock et al, 2019;Caliskan et al, 2017;Kim and Tinoco, 2017;Larsen et al, 1997;Tsuchihashi and Brown, 1992). The FSS from HIV also stalls the ribosome in the NR conformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Mutations in the slippery sequence of dnaX were shown to decrease frameshifting efficiency to low ( 5%) or undetectable levels (Bock et al, 2019;Caliskan et al, 2017;Kim and Tinoco, 2017;Larsen et al, 1997;Tsuchihashi and Brown, 1992). The FSS from HIV also stalls the ribosome in the NR conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The FSS is an RNA hairpin or a pseudoknot (Atkins et al, 2001). The slippery sequence allows cognate pairing of the P-site and A-site tRNAs in both 0 and -1 frames and thus makes frameshifting thermodynamically favorable (Bock et al, 2019). The mechanism by which FSS stimulates frameshifting is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Since these studies have shown that in children with ASD the right parietal lobe deals with the processing of language content, this consequently implies difficulties in maintaining attention and emotional processing, since in children who develop normally these processes take place almost exclusively in the right hemisphere. Reduced degree of asymmetry in cerebral cortex thickness in a total of 1774 children with ASD compared with 1809 control peers from 54 independent data sources was confirmed for medial part of the frontal lobe, orbitofrontal cortex, cingulum and lower part of the parietal cortex [ 217 ].…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…[3][4][5][6][7] During this pause, the t-RNA that is annealed within the ribosomal P-site (and most often also the t-RNA in the A-site) 8 begin to sample alternative base pairing interactions that shift the reading frame of the ribosme. 9 Based on these mechanistic considerations, PRF is typically believed to be mediated at the level of RNA structure. Nevertheless, recent reports have also found that the efficiency of PRF can be tuned by a variety of regulatory proteins and/ or miRNA.…”
Section: Introductionmentioning
confidence: 99%